Supplementary Motor Complex and Disturbed Motor Control – a Retrospective Clinical and Lesion Analysis of Patients after Anterior Cerebral Artery Stroke - Brugger, Florian; Galovic, Marian; Weder, Bruno J.; Kägi, Georg (Frontiers in Neurology, 2015)
Background: Both the supplementary motor complex (SMC), consisting of the supplementary motor area (SMA)-proper, the pre-SMA and the supplementary eye field, and the rostral cingulate cortex (ACC) are supplied by the anterior cerebral artery (ACA) and are involved in higher motor control. The Bereitschaftspotential (BP) originates from the SMC and reflects cognitive preparation processes before volitional movements. ACA strokes may lead to impaired motor control in the absence of limb weakness and evoke an alien-hand syndrome (AHS) in its extreme form. Aim: To characterize the clinical spectrum of disturbed motor control after ACA strokes including signs attributable to AHS and to identify the underlying neuroanatomical correlates. Methods: A clinical assessment focusing on signs of disturbed motor control including intermanual conflict (i.e. bilateral hand movements directed at opposite purposes), lack of self-initiated movements, exaggerated grasping, motor perseverations, mirror movements and gait apraxia was performed. Symptoms were grouped into A) AHS specific and B) non-AHS specific signs of upper limbs and C) gait apraxia. Lesion summation mapping was applied to the patients’ MRI or CT scans to reveal associated lesion patterns. The BP was recorded in two patients. Results: Ten patients with ACA strokes (9 unilateral, 1 bilateral; mean age: 74.2 years; median NIH-SS at admission: 13.0) were included in this case series. In the acute stage, all cases had marked difficulties to perform volitional hand movements, while movements in response to external stimuli were preserved. In the chronic stage (median follow-up: 83.5 days) initiation of voluntary movements improved, although all patients showed persistent signs of disturbed motor control. Impaired motor control is predominantly associated with damaged voxels within the SMC and the anterior and medial cingulate cortex, while lesions within the pre-SMA are specifically related to AHS. No BP was detected over the damaged hemisphere. Conclusion: ACA strokes involving the premotor cortices, particularly the pre-SMA, are associated with AHS-specific signs. In the acute phase, motor behaviour is characterized by the inability to carry out self-initiated movements. Motor control deficits may persist to a variable degree beyond the acute phase. Alterations of the BP point to an underlying SMC dysfunction in AHS.